Resistência de Haemonchus placei, Cooperia punctata e Oesophagostomum radiatum à ivermectina pour-on a 500mcgkg-1 em rebanhos bovinos no Brasil - Zanetti Lopes, Welber Daniel [UNESP]; Felippelli, Gustavo [UNESP]; Pires Teixeira, Weslen Fabricio [UNESP]; Cruz, Breno Cayeiro [UNESP]; Maciel, Willian Giquelin [UNESP]; Buzzulini, Carolina [UNESP]; Shigaki de Matos, Lucas Vinicius [UNESP]; Costa Gomes, Lucas Vinicius [UNESP]; Melo Pereira, Joao Carlos [UNESP]; Favero, Flavia Carolina [UNESP]; Oliveira, Gilson Pereira de [UNESP]; Costa, Alvimar Jose da [UNESP] (Univ Federal Santa Maria, 2014)
The broad spectrum of endectocides and the easy use mode of their pour-on formulations are factors that have stimulated a higher frequency of use these drugs in cattle. In this study was evaluated the efficacy of ivermectin pour-on using the dose of 500mcgkg(-1), against nematodes in naturally infected cattle from different herds. Twelve calves were brought from each of the four farms selected. All the 48 calves used showed mean of eggs per gram of feces (EPG) greater than 500 considering three consecutive counts. Subsequently, animals from each herd were divided into two groups of six animals each, one treated pour-on with ivermectin 500mcgkg(-1) and other kept as untreated control. Calves were euthanized 14 days after treatment for counting the endoparasites. Ivermectin showed null effect against H. placei in all the herds evaluated. The drug was also ineffective against C. punctata in the herds from Jaboticabal, SP and Formiga, MG, and reached efficacy of 75.8% and 58.4% in herds from Sao Jose do Rio Pardo, SP and Sao Sebastiao do Para so, MG, respectively. Efficacies of 94.2% (Jaboticabal), 0.0% (Sao Jose do Rio Pardo), 94.2% (Formiga) and 39.2% (Sao Sebastiao do Para so) were detectedagainstO. radiatum. Based on these results obtained on the present study, the four populations of Haemonchus placei and Cooperia punctata evaluated were resistant to ivermectin pour-on using a dose of 500mcgkg(-1). Ivermectin-resistant strains of Oesophagostomum radiatum were found in two of the four herds evaluated.
Haemonchus placei, Cooperia punctata and Oesophagostomum radiatum resistant to ivermectin pour-on 500mcgkg(-1) in cattle from Brazil
Keywords: gastrointestinal nematodes; macrocyclic lactones; multiple resistance; ruminants; topically